Helminthocoenosis of the house mouse (mus musculus l., 1758) in transformed landscape of Osh-Karasui oasis (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
As a result of the study, it was established that among the mouse-like rodents living in the transformed landscapes of the Osh-Karasu oasis, house mice (Mus musculus) dominate. In the studied animals, 12 species of helminths belonging to three classes of parasitic worms were identified. The largest number of species is accounted for by nematodes - 9 species, the smallest number of species is in acanthocephala - 1 species. It should be especially emphasized that in these stations, among house mice, both in the number of species (9) and in the number of individuals (925), the dominant position is occupied by nematodes of the family Syphacidae, which can parasitize humans and animals.
Keywords: transformed landscapes, synanthropic rodents, parasite community, Mus musculus, Syphacidae, endoparasites